Reconstruction of a Сommunicative Stereotype as Source of Information on Identification Mechanisms of Cultures of England and Germany - E. E. Rybakova (Vestnik MGIMO-Universiteta, 2013)
This article considers communicative stereotypes of cross-cultural communication of England and Germany taking as a source literary work of the beginning of the XX century. As communicative stereotype is a source of information about axiolgical constituent part of «cultural code», its reconstruction on different levels of existence including its consideration in “the mirror” of another culture is an important means of optimization of cross-cultural interaction.